Aliran Al-Maturidi dan Al-Maturidiyyah dalam Dunia Islam - Wan Ali, Wan Zailan Kamaruddin (Jurnal Usuluddin, 1998)
As the title indicates, the aim of this article is to discuss the establishment of al-Maturidi and al-Maturidiyyah sect in the Muslim world. As far as the topics are concerned, they will be in two parts. First part will deal with the background of al-Maturidi and al-Maturidiyyah and their thoughts as compared to al-Asy’ari and al-Asya’irah, whereas the second part will stress on its development and impact to the Muslim people in the Muslim world.